As I Remember: George M. Drumm (1967)
George P. Cooper's interview with George M. Drumm, a former faculty member of the Cal Poly dairy department. [00:00:13] As I Remember Opening [00:00:26] Drumm recalls his first contact with Cal Poly and how he heard about it [00:01:14] Drumm describes the students and facilities at Cal Poly in 1935 [00:01:49] Drumm recalls the small number of faculty and staff members and the lack of funding [00:02:25] Drumm recalls working for the Bureau of Vocational Education while also working at Cal Poly [00:03:15] Drumm describes his goals that he set out for the dairy department, such as increasing enrollment, and how he went about accomplishing it [00:04:21] Drumm recalls the results of his efforts to increase enrollment and the effect of the Depression on enrollment [00:05:17] Drumm recalls the high point in enrollment after World War II [00:05:43] Drumm describes his objective in developing a high-class dairy herd [00:06:28] Drumm the benefits of having outstanding dairy cattle [00:07:16] Drumm describes what he accomplished with his dairy herd [00:08:04] Drumm describes the butter fat production with the herd at Cal Poly [00:09:04] Drumm recalls selling stock to Future Farmers and mature breeders and the reputation of the program internationally [00:10:20] Drumm discusses the initial lack of proper facilities [00:11:16] Drumm discusses the addition of new facilities, such as a dairy plant [00:12:05] Drumm recalls the practicality of the facilities [00:12:50] Drumm describes how the dairy department went about paying its own operating expenses through cattle sales and milk sales [00:14:18] Drumm recalls training judges in dairy products and dairy cattle [00:15:00] Drumm describes the contest at Waterloo [00:15:30] Drumm discusses other contests in which his dairy team competed [00:16:04] Drumm describes some of his students and the work that they entered [00:18:00] Drumm discusses his students going into teaching high school agriculture education [00:18:43] Drumm discusses his students entering veterinary medicine [00:19:05] Drumm recalls helping with the students' project animals [00:20:30] Drumm describes making high-quality seed stock available to students, graduates, and breeders [00:22:39] Drumm recalls how much money he had to purchase a bull [00:23:44] Drumm recalls visiting the places of origin of certain breeds of dairy cows [00:24:50] Drumm reflects on his career [00:25:50] Interview wrap-up and As I Remember Closing